PENGARUH IKLIM ORGANISASI TERHADAP KEPUASAN KERJAKARYAWAN BIRO SDM DAN UMUM PADAPT KERTAS PADALARANG (PERSERO) - Nita Rachmayati, - (2011)
The success of the company in achieving its objectives because of the role of employees. Employees not only as objects in the achievement of goals, but also into the subject or perpetrator. They can be a planner, implementer and controller that always plays an active role in achieving corporate objectives as well as having thoughts, feelings and desires that could affect his attitude toward work. Employees contribute to the company the ability, expertise and skills possessed while rewarding the company and reward employees fairly so as to give satisfaction. Problems arising in this research is on the low job satisfaction. If this phenomenon is not handled properly, it will be able to hurt the company. Subjects in this study are employees of the bureau human resources and general of PT Kertas Padalarang (Persero). With the independent variable is the organizational climate and the dependent variable is job satisfaction. The purpose of this research is to study and learn: 1) organizational climate of the bureau human resources and general of PT Kertas Padalarang (Persero), 2) Job satisfaction employees of the bureau human resources and general of PT Kertas Padalarang (Persero), and 3) The influence organizational climate to the job satisfaction employees of the bureau human resources and general of PT Kertas Padalarang (Persero). The research method used was survey research method with a sample of 55 respondents. The data analysis technique used was simple linear regression analysis. The results showed that organizational climate of the bureau human resources and general of PT Kertas Padalarang (Persero) is in conducive enough category and job satisfaction in middle category. Result of calculation correlation coefficient between organizational climate and job satisfaction is of 0.484 means that there is a medium between organizational climate with job satisfaction. In other word, organizational climate plays a considerable role to increase job satisfaction. Therefore, in order to increase job satisfaction employees of the bureau human resources and general of PT Kertas Padalarang (Persero), companies need to create a conducive organizational climate.